Recommendations of the German Radiological Society’s breast imaging working group regarding breast MRI - Wenkel, Evelyn; Wunderlich, Petra; Fallenberg, Eva Maria; Platz Batista da Silva, Natascha; Preibsch, Heike; Sauer, Stephanie; Siegmann-Luz, Katja; Weigel, Stefanie; Wessling, Daniel; Wilpert, Caroline; Baltzer, Pascal Andreas Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Citation FormatZitierweise
Keywords: breast; MR-diffusion/perfusion; MR-imaging; imaging sequences